Early caregiver burden in owners of pets with suspected cancer: Owner psychosocial outcomes, communication behavior, and treatment factors - Shaevitz, Marejka H. (J Vet Intern Med, 2020)
BACKGROUND: Owners of companion animals with serious illnesses are likely to experience “caregiver burden.” This topic has not been fully evaluated in veterinary oncology. OBJECTIVES: To examine owners of a dog or cat with suspected cancer for relationships between early caregiver burden and (a) psychosocial factors: depression, stress, and quality of life; (b) owner communication behavior; and (c) specific pet treatment plan factors. ANIMALS: None. METHODS: This cross‐sectional, observational study recruited 164 owners of a cat or dog presenting for evaluation by a veterinary oncology service at a single referral institution. Measures of caregiver burden, psychosocial function, treatment plan elements, and demographics were collected online via owner self‐report. Medical records were reviewed to identify factors including diagnosis, medications, treatment schedules, and owner communications. RESULTS: Caregiver burden correlated with higher stress (r (s) = 0.40, P < .001), greater symptoms of depression (r (s) = 0.50, P < .001), and lower quality of life (r (s) = 0.39, P < .001). Pet treatment plan factors related to caregiver burden included changes in care routines, perception that compliance with new routines was challenging, and difficulty adhering to medication routines. There was low correlation between caregiver burden and owner‐driven communications (r (s) = 0.15, P = .07). CONCLUSIONS AND CLINICAL IMPORTANCE: Findings suggest caregiver burden is similar in owners of pets with cancer and owners of pets with other diseases. Caregiver burden is present in the earliest stages of disease. Major correlates of burden including life‐disruptive treatments and schedules provide key areas for potential intervention by veterinary teams.